EU General Data Protection Regulation (GDPR), Third Edition : an Implementation and Compliance Guide. - IT Governance, I. T. (IT Governance Ltd, 2019)
EU GDPR - An Implementation and Compliance Guide is a perfect companion for anyone managing a GDPR compliance project. It explains the changes you need to make to your data protection and information security regimes and tells you exactly what you need to do to avoid severe financial penalties.